One day course of Mobile Apps Development at Kolej Komuniti Kuala Pilah / Jamaliah Mohd Taib and Norlida Othman - Mohd Taib, Jamaliah; Othman, Norlida (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
On 25th March 2021, 14 lecturers from FSKM Kampus Kuala Pilah had attended a one-day course on Mobile Apps Development at Kolej Komuniti Kuala Pilah. The purpose of the course is to develop mobile apps by using Google Sites and Thunkable apps. Thunkable is an app that will enable anyone to create a beautiful and powerful mobile app as simple as doing "drag and drop" actions. The course starts with creating a few web pages using the Google Sites platform and later, linking the web pages to the mobile app created using the Thunkable apps.